(untitled) (The Research of Medical Science Review, 2025)
Objective: To Compare the efficacy of Mineral Trioxide Aggregate (MTA) and Ferric Sulfate (Fs) as Pulpotomy Medicaments for Primary Molars Study design: Randomized Controlled Trials Place of the study: Department of Operative Dentistry and endodontics, Nishter Institute of Dentistry, Multan Methodology: A total of 90 Patients were included and were divided into two groups using lottery method. Group-A received FS and Group-B received MTA. All the patients were called at 1, 3 months of post treatment and were further followed up for 6 months postoperatively and will be assessed for efficacy of the treatment. Statistical Package for the Social Sciences (SPSS-26) version was used to analyze that data. Mean and standard deviation was calculated for age. Frequencies and percentages were reported for categorical variables like gender and outcome (efficacy). Chi-square test was applied to compare the outcome between the two groups. P-value < 0.05 will be taken as significant. Results: Mineral trioxide aggregate (MTA) was found to be effective in 45 (100%) cases as compared to FS in 28 (62%) cases with statistically significant difference = 0.000 Conclusion: Both FS and MTA had comparable clinical and radiographic performance at one month as pulpotomy medicaments. However, at 6 months, MTA showed higher radiographic and overall success as a pulpotomy medicament in primary molars compared to FS. As a result, MTA can be suggested as an appropriate medication for pulpotomies in primary molars.